Short-Term Outcomes Following Hip Fractures in Patients at Least 100 Years Old. (5th July 2017) - Manoli, Arthur; Driesman, Adam; Marwin, Rebecca A.; Konda, Sanjit; Leucht, Philipp; Egol, Kenneth A.
Abstract : Background: The number of hip fractures is rising as life expectancy increases. As such, the number of centenarians sustaining these fractures is also increasing. The purpose of this study was to determine whether patients who are ≥100 years old and sustain a hip fracture fare worse in the hospital than those who are younger. Methods: Using a large database, the New York Statewide Planning and Research Cooperative System (SPARCS), we identified patients who were ≥65 years old and had been treated for a hip fracture over a 12-year period. Data on demographics, comorbidities, and treatment were collected. Three cohorts were established: patients who were 65 to 80 years old, 81 to 99 years old, and ≥100 years old (centenarians). Outcome measures included hospital length of stay, estimated total costs, and in-hospital mortality rates. Results: A total of 168, 087 patients with a hip fracture were identified, and 1, 150 (0.7%) of them had sustained the fracture when they were ≥100 years old. Centenarians incurred costs and had lengths of stay that were similar to those of younger patients. Despite the similarities, centenarians were found to have a significantly higher in-hospital mortality rate than the younger populations (7.4% compared with 4.4% for those 81 to 99 years old and 2.6% for those 65 to 80 years old; p < 0.01). Male sex and an increasing number of medical comorbidities were found to predict in-hospital mortality for centenarians sustaining extracapsular hip fractures. No significant predictors of in-hospital mortality were identified for centenarians who sustained femoral neck fractures. An increased time to surgery did not influence the odds of in-hospital mortality. Conclusions: Centenarians had increased in-hospital mortality, but the remaining short-term outcomes were comparable with those for the younger cohorts with similar fracture patterns. For this extremely elderly population, time to surgery does not appear to affect short-term mortality rates, suggesting a potential benefit to preoperative optimization. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.